The Future of Thermal Comfort in an Energy- Constrained World - Law, Tim.; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
The dissertation investigates the scientific and business factors that have resulted in air-conditioning being a major contributor to climate-change. With his architectural background, the author demonstrates how a design methodology, not commonly adopted in scientific studies, may actually be a suitable way of dealing with a complex problem: the 'business as usual' scenario involving building science, sociological values and consumer behavior. Using his innovations as case studies, the author shows how good ideas cannot be evaluated on scientific merit alone and demonstrates why commercialization may have a pivotal role in deployment of research-based technology. He advances the theory of personalized thermal comfort which can potentially resolve the air-conditioning conundrum.
The State of the World -- Literature Review: Thermal Comfort and Air-Conditioning -- Brain Cooling -- Comfort Energetics $1 (BThermal Comfort Under Energy Constraints.-Research Methodology -- The Rain Tower -- Finding a market-oriented solution -- Personal air-conditioning -- Field Testing DTAC, Methodology & Results -- Future Research -- Future Research.s
Keywords: Engineering; Engineering; Building Construction; Climate Change Management and Policy; Energy Efficiency (incl. Buildings).; Market Research